2013
DOI: 10.1039/c3tc00869j
|View full text |Cite
|
Sign up to set email alerts
|

Copper oxide quantum dot ink for inkjet-driven digitally controlled high mobility field effect transistors

Abstract: Copper oxide (CuO) quantum dots (QDs) having a diameter of 5-8 nm were synthesized by a simple solution process. The as-synthesized QDs showed a highly crystalline monoclinic phase of CuO with a bandgap of $1.75 eV. The CuO QDs were further formulated as an ink for inkjet printing of CuO field effect transistors (FETs). The ink-jetting behavior of the as-formulated ink samples showed that the CuO concentration and digitally controlled number of over-prints are important factors for optimizing the uniformity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 61 publications
2
36
0
Order By: Relevance
“…Research on Cu 2 O has a long history, and the fabrication of Cu 2 O thin films or nanostructures has been widely reported by various techniques, such as PLD, magnetron sputtering, and thermal oxidation; and chemical routes, such as electrodeposition, spin coating, atomic‐layer deposition, spray coating, molecular‐beam epitaxy, microwave irradiation from a Cu precursor, chemical vapor deposition, and ink printing . A summary of the most promising studies on binary copper oxide thin films is shown in Table 2 .…”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on Cu 2 O has a long history, and the fabrication of Cu 2 O thin films or nanostructures has been widely reported by various techniques, such as PLD, magnetron sputtering, and thermal oxidation; and chemical routes, such as electrodeposition, spin coating, atomic‐layer deposition, spray coating, molecular‐beam epitaxy, microwave irradiation from a Cu precursor, chemical vapor deposition, and ink printing . A summary of the most promising studies on binary copper oxide thin films is shown in Table 2 .…”
Section: Discovery and Synthesis Of Hole‐transporting (P‐type) Oxidesmentioning
confidence: 99%
“…Vaseem et al reported a high‐performance CuO‐based TFT by the inkjet‐printing technique . Copper acetate dihydrate [Cu(CH 3 COO) 2 ·2H 2 O] was used as the precursor.…”
Section: Performance Of P‐type Oxide Thin‐film Transistorsmentioning
confidence: 99%
“…The position of the Raman peaks associated with the B1g and A1g vibration modes of TiO2 was influenced by the CuO modification in CuO-TiO2 NTs compared to pristine TiO2 NTs, as can be seen in Figure 7b. However, in addition to the scattering peaks which are assigned to the anatase phase of TiO2, another peak centered at 274 cm −1 is clearly observed (Figure 7c) and is attributed to the CuO phase [49] which is dispersed on TiO2 NTs (Figures 1c,d and 2b). Because of the negative shift of the XPS peaks of Ti 2p to a lower binding energy and the blue shift of the Eg Raman mode of TiO2, it is reasonable to conclude the slight formation of partially-reduced Ti species (Ti 4+ ) by the free electrons left from the oxygen vacancies formed in the CuO-TiO2 NTs.…”
Section: Metal-support Interactionsmentioning
confidence: 99%
“…14,15 Bulk CuO is known to exhibit antiferromagnetic 16 and multiferroic behavior at low temperature. 19 CuO was earlier synthesized in different dimensions (1-D, 2-D, 3-D), but 1-D nanostructures assume significant importance in regard to their increased efficiency in the transport of electrons and controlled optical and magnetic behavior which have applications in solar cells, 20,21 sensors, [22][23][24] FETs, 25 the next generation Na-ion batteries 26 and spintronic devices. 19 CuO was earlier synthesized in different dimensions (1-D, 2-D, 3-D), but 1-D nanostructures assume significant importance in regard to their increased efficiency in the transport of electrons and controlled optical and magnetic behavior which have applications in solar cells, 20,21 sensors, [22][23][24] FETs, 25 the next generation Na-ion batteries 26 and spintronic devices.…”
Section: Introductionmentioning
confidence: 99%